UPAYA PENGUATAN PROGRAM STIMULASI, DETEKSI DAN INTERVENSI DINI TUMBUH KEMBANG (SDIDTK) DENGAN MENGGUNAKAN PENDEKATAN BUKU RAPOR SEHATKU - Yuliani S, Ayu; Zaitun, Zaitun; Suhartini, Suhartini (LPPM Universitas Bina Bangsa, 2024)
The Community Partnership Program activities are expected to produce something innovative in the implementation of its activities. Sitopeng Health Center in Cirebon City adopted an innovative approach in improving early detection and intervention of child development problems by utilizing Rapor Sehatku. This program aims to identify children at risk of experiencing developmental disorders early and provide appropriate stimulation and intervention. This Community Partnership Program (PKM) involves collaboration between health workers, parents, and PAUS teachers in paying attention to the growth and development of children at preschool age. Parents are empowered to understand the importance of their role in stimulating child development and gaining knowledge and skills. Rapor Sehatku is the main instrument in this program, which records children's development periodically. By using this book, parents, PAUD teachers and health workers can monitor child development in a more structured manner and identify early on the possibility of developmental disorders, especially in early detection of stunting. The implementation of this PKM activity is carried out in the form of training activities and direct practice on how to detect child development in parents and PAUD teachers at Mutiara Bangsa Kindergarten. This aims to increase parents' awareness and understanding of the importance of their role in supporting optimal child development. The results of this community service show an increase in knowledge and enthusiasm of parents, especially mothers who have children of preschool age and the detection of child growth and development, the use of the healthy report book becomes a link for parents and PAUD teachers in monitoring the growth and development of preschool children. The results of the validation activities show that training using the Healthy Report Book is able to improve the Early Growth and Development Stimulation, Detection and Intervention Program